Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 192203 by naka3546 last updated on 11/May/23

Answered by HeferH last updated on 11/May/23

(3h−2x)2h = 3hx   6h^2 −4hx = 3hx   6h^2 = 7hx   6h = 7x   ((6h)/7) = x   ((ON)/(NB)) = ((3h−((6h)/7))/(2h+((6h)/7))) = (((21h−6h)/7)/((14h+6h)/7)) = ((15h)/7)∙(7/(20h)) = (3/4)

$$\left(\mathrm{3h}−\mathrm{2x}\right)\mathrm{2h}\:=\:\mathrm{3hx} \\ $$$$\:\mathrm{6h}^{\mathrm{2}} −\mathrm{4hx}\:=\:\mathrm{3hx} \\ $$$$\:\mathrm{6h}^{\mathrm{2}} =\:\mathrm{7hx} \\ $$$$\:\mathrm{6h}\:=\:\mathrm{7x} \\ $$$$\:\frac{\mathrm{6h}}{\mathrm{7}}\:=\:\mathrm{x} \\ $$$$\:\frac{\mathrm{ON}}{\mathrm{NB}}\:=\:\frac{\mathrm{3h}−\frac{\mathrm{6h}}{\mathrm{7}}}{\mathrm{2h}+\frac{\mathrm{6h}}{\mathrm{7}}}\:=\:\frac{\frac{\mathrm{21h}−\mathrm{6h}}{\mathrm{7}}}{\frac{\mathrm{14h}+\mathrm{6h}}{\mathrm{7}}}\:=\:\frac{\mathrm{15h}}{\mathrm{7}}\centerdot\frac{\mathrm{7}}{\mathrm{20h}}\:=\:\frac{\mathrm{3}}{\mathrm{4}}\: \\ $$

Commented by HeferH last updated on 11/May/23

Commented by naka3546 last updated on 12/May/23

Thank  you

$$\mathrm{Thank}\:\:\mathrm{you} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com